Street Gangs and Interventions: Innovative Problem Solving with Network Analysis - Jean McGloin (My University, 2016)
This paper briefly reviews the range of prevention, intervention, suppression, and comprehensive strategies, providing examples of each type. It then offers a case study of problem analysis in Newark, New Jersey. The reader will learn the unique utility of network analysis in the resultant problem analysis and understand the important role of an academic research partner. Finally, the paper considers the importance of sustainability with regard to problem analysis.